1984
DOI: 10.1210/endo-115-4-1239
|View full text |Cite
|
Sign up to set email alerts
|

Aging and Dietary Modulation of Rat Skeleton and Parathyroid Hormone*

Abstract: Studies were carried out on SPF F344 male rats to evaluate the effects of aging and life-prolonging food restriction, without malnutrition, on rat skeleton and circulating PTH. Six-week-old F344 rats were divided into five groups. Group 1 rats were fed ad libitum a diet that contained 21% protein. Group 2 rats were fed 60% of the mean food intake of group 1 rats from 6 weeks of age for the rest of their lives. Group 3 rats were fed 60% of the ad libitum food intake until 6 months of age and then switched to ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

1986
1986
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(25 citation statements)
references
References 18 publications
3
21
1
Order By: Relevance
“…The greater increase in the SSI values of long bones and the change in first lumbar vertebra might be due to these morphological changes. This might be related to almost no change in organic components with increasing age [11,[13][14]. The age when rats show the so-called peak of bone mass in the whole skeleton was not clearly determined from the results obtained in this study.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The greater increase in the SSI values of long bones and the change in first lumbar vertebra might be due to these morphological changes. This might be related to almost no change in organic components with increasing age [11,[13][14]. The age when rats show the so-called peak of bone mass in the whole skeleton was not clearly determined from the results obtained in this study.…”
Section: Discussionmentioning
confidence: 77%
“…According to previous studies, the high BMD or calcium content of the first and fourth lumbar vertebrae, femur, and tibia coincided with a high testosterone level at the age of 12 months in male Wistar rats [11,14,17]. On the other hand, no change in the BMD of the femur measured by DEXA in male rats was observed after the rats had reached maturity [19].…”
Section: Discussionmentioning
confidence: 87%
“…brain maturation could be compared at similar ages in calorically restricted and normal model organisms. In support of this view, the effects of caloric restriction show a decrease in the normal rate of maturation in both rodents (Kalu et al, 1984;Merry & Holehan, 1981) and rhesus monkeys (Mattison et al, 2003). Interestingly, caloric restriction seems to have reduced effects on longevity if applied after middle age, i.e.…”
Section: Caloric Restrictionmentioning
confidence: 85%
“…The earliest study (McCay et al 1935) found that femurs removed from restricted (R) rats crumbled during dissection; however, the level of CR makes it likely that these animals were suffering from nutritional deficiencies. Later studies by Kalu et al (1984aKalu et al ( , b, 1988 in F344 rats under a less severe restriction found that CR resulted in delayed epiphyseal closure, bones of lower density, and no reduction in femur density in old age. Results from more recent rodent studies have been variable.…”
Section: Introductionmentioning
confidence: 95%